2022
DOI: 10.1039/d2dt02571j
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the tethered unhooking and rehooking of S2B in the reaction domain of FeMo-co, the active site of nitrogenase

Abstract: Energetically accessible reversible unhooking of S2B or S2BH from Fe2, as an intrinsic property of FeMo-co, needs to be considered in the formulation of mechanisms for the reactions of nitrogenase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…This isomer is predicted to be relatively high in energy (11.7 kcal/ mol using the QM-VI region) compared to E 2 -SH − @Fe6, likely due to steric repulsion involving the terminal SH − group and His195. This makes it an unlikely candidate for the E 2 state (previous results 12,30,35,40 also found a similar trend); however, as the results for E 0 and E 1 have revealed, stronger binding is found to Fe6 than Fe2, making N 2 binding to such a geometry with an open coordination site to Fe6 of interest.…”
Section: Nmentioning
confidence: 68%
See 1 more Smart Citation
“…This isomer is predicted to be relatively high in energy (11.7 kcal/ mol using the QM-VI region) compared to E 2 -SH − @Fe6, likely due to steric repulsion involving the terminal SH − group and His195. This makes it an unlikely candidate for the E 2 state (previous results 12,30,35,40 also found a similar trend); however, as the results for E 0 and E 1 have revealed, stronger binding is found to Fe6 than Fe2, making N 2 binding to such a geometry with an open coordination site to Fe6 of interest.…”
Section: Nmentioning
confidence: 68%
“…15 A QM/MM study (using the TPSSh functional) from our research group in contrast suggested E 4 models with two bridging hydrides located on the same pair (SP) of Fe ions (Fe2 and Fe6) and with open belt sulfur bridges (terminal sulfhydryl groups) that were found to be energetically more favorable than models with closed belt sulfur bridges (including E 4 -DP-Fe2/6(5)). Such opening of protonated belt sulfides has also been discussed in computational work by Dance, 40 Raugei, 13 and recently by Ryde and co-workers. 35 Kinetic and spectroscopic studies 7,37,41−44 indicate that dinitrogen will bind to the E 4 state, while no binding has been directly observed in earlier E n states (with the role of E 3 unclear).…”
Section: Introductionmentioning
confidence: 70%
“…These variables are shown on Chart 1. Not all combinations are possible: exo -Fe6–H impedes unhooking of S2B from Fe2, 39 and an intact Fe2–S2B–Fe6 bridge together with an Fe2–H–Fe6 bridge leaves no space for the binding of reducible N 2 . An H atom on S2B is included in all calculated structures due to its better calculated energy.…”
Section: Resultsmentioning
confidence: 99%
“…31–38 I have analysed the factors that influence this unhooking, and described the unhooking of S2B (or S2BH) from Fe2, tethered to Fe6, and the rehooking reaction. 39 2H + + 2e − → H 2 N 2 + 6H + + 6e − → 2NH 3 D 2 + 2H + + 2e − → 2HD…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently with this bridge formation, S2BH unhooks its bond to Fe2 and eventually is more than 3.2 Å from Fe2. Unhooking of S2B from Fe2 is a general property of ligated FeMo‐co, and the factors that influence it have been expounded, and the potential energy surfaces for interconversions of hooked and unhooked isomers described [21e] . In general the energy differences between hooked and unhooked isomers are <10 kcal mol −1 , and kinetic barriers for interconversions are up to 13 kcal mol −1 .…”
Section: Resultsmentioning
confidence: 99%